Construction and Validation of a Measurement Instrument for Attitudes towards Teamwork - Mendo-Lázaro, Santiago; Polo-del-Río, María I.; Iglesias-Gallego, Damián; Felipe-Castaño, Elena; León-del-Barco, Benito (Frontiers in Psychology, 2017)
Cooperative, collaborative learning and other forms of group learning methods are increasingly used in classrooms. Knowing students’ attitudes toward teamwork has great value since they influence the students’ learning results as well as their social development. So it is necessary to have robust instruments to provide a better understanding of these attitudes and preferences concerning teamwork. Such instruments also help to identify the factors that promote positive or negative attitudes within the context of group activities. Using a sample of 750 first and second year university students studying a degree in Kindergarten, Primary and Social Education, an instrument measuring attitudes toward team learning has been developed. Two distinct factors were obtained through various factorial analyses and structural equations: Academic attitudes and Social and emotional attitudes. Our study reveals that the instrument is both valid and reliable. Its application is both simple and fast and it has important implications for planning teaching and learning activities that contribute to an improvement in attitudes as well as the practice of teaching in the context of learning through teamwork.